Fast tracking the SADC integration agenda to unlock regional collaboration gains along growth corridors in Southern Africa - Alexis Habiyaremye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Despite more than two decades of economic integration efforts, levels of spatial development inequality remain high within the Southern African Development Community (SADC). Owing to persistent delays in the implementation of the SADC integration agenda, infrastructure connectivity is still overly inefficient, while cumbersome customs also continue to impede the free movement of goods and services. This hampers the growth potential of planned spatial development initiatives in the region. This study aims to analyse how the development of regional growth corridors and the deepening of SADC integration could help to ease existing connectivity bottlenecks and unlock the dynamic gains of closer intra-regional collaboration for shared growth. It examines the structural challenges to the emergence of dynamic growth corridors and probes the potential for overcoming them through territorial collaboration between metropolitan clusters and rural areas connected by transport corridors. The development of growth corridors requires the adoption of new production techniques and the application of concomitant skills and know-how. This study therefore also explores the absorptive capacity requirements for structural transformation and surveys existing facilities and incentives for technological capability building.
Keywords: O13; O14; R12; R42; 330; growth corridors; intra-regional trade; regional integration; Southern African Development Community (SADC); structural transformation